Pengaruh Media Sosial Terhadap Motivasi Belajar Sejarah Siswa Kelas XII SMK Kasimo Sumba - Soleman D. Kaka; Astuti Rangu; Nikodemus N.G.Tuna; Marlinus G. Ate; Maria I.I.Talu (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
History is one of the important subjects in education in Indonesia. Studying history can help students understand the development of the nation and the noble values ​​contained therein. However, today's reality is that students tend to find it difficult and are not interested in history lessons. Because of the influence of several things such as technological developments, especially in social media, have a big influence on generation Z today, Based on the research results, it shows that social media, learning motivation has the highest and lowest values ​​for each variable. The organizational culture variable has the highest score for the mutual respect indicator from the research results showing a mean of 3.42 and the lowest score for the full initiative indicator from the research results shows a mean of 2.73. The social media variable has the highest score for the indicator of working in a team from the research results showing a mean of 3.30 and the lowest score for the indicator of mastery of work equipment from the research results shows a mean of 2.96. The motivation variable has the highest score for the productivity indicator from the research results showing a mean of 3.23 and the lowest score for the independence consideration indicator from the research results shows a mean of 2.65.